The Influence of Work Discipline, Supervision and Work Stress on Employee Performance at PT Yose Andalan Melayu Pangkalan Kerinci - Yunanda, Syalya Chantika; Garnasih, Raden Lestari; Nasution, Hafiza Oktasia (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This study aims to determine the influence of work discipline, supervision and job stress on employee performance at PT Yose Andalan Melayu Pangkalan Kerinci. The type of data in the research used is quantitative. The population in this study includes all employees at PT Yose Andalan Melayu Pangkalan Kerinci. The sampling technique used in this study is a saturated sample with a sample size of 53 employees at PT Yose Andalan Melayu Pangkalan Kerinci. The data was collected with the help of a questionnaire and then the data was processed by multiple linear regression analysis with the help of SPSS version 22 software. The results showed that: 1) Work discipline has a significant positive effect on employee performance at PT Yose Andalan Melayu Pangkalan Kerinci. 2) Supervision has a significant positive effect on employee performance at PT. Yose Mainstay Melayu Pangkalan Kerinci. 3) Job Stress has a negative and insignificant effect on employee performance at PT. Yose Mainstay Melayu Pangkalan Kerinci. 4) Work discipline, supervision and job stress simultaneously have a significant positive effect on employee performance at PT. Yose is the mainstay of the Malays of Pangkalan Kerinci.